2007
DOI: 10.1016/j.pbb.2007.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced sensitivity to naltrexone-induced drinking suppression of fluid intake and sucrose consumption in maternally separated rats

Abstract: Early-life stress has been identified as a risk factor in the development of a host of disorders, including substance abuse; however the link between early postnatal stress and changes in measures of reward has not been thoroughly researched. The current study had two main objectives: 1) to determine the impact of maternal separation (an animal model of early-life stress) on the consumption of 10% and 2.5% sucrose solutions by Long-Evans rat dams and male and female offspring, and 2) to determine the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 53 publications
(54 reference statements)
0
14
0
1
Order By: Relevance
“…The effect of a diet rich in carbohydrates on weight gain is not clear from the literature since it has been reported to increase (38,46), decrease (9,22,28,36), or have no effect (2,13,21,39,49,50,52,62) on BW. These contrasting outcomes could be due to differences in species, sex, type of carbohydrate, the age that the diet was introduced, or the length of exposure to the diet.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of a diet rich in carbohydrates on weight gain is not clear from the literature since it has been reported to increase (38,46), decrease (9,22,28,36), or have no effect (2,13,21,39,49,50,52,62) on BW. These contrasting outcomes could be due to differences in species, sex, type of carbohydrate, the age that the diet was introduced, or the length of exposure to the diet.…”
Section: Discussionmentioning
confidence: 99%
“…However, quantification of anhedonia involving a sucrose reinforcer under baseline conditions has yielded inconsistent results. For example, most published reports indicate that maternal separation in rodents does not affect sucrose consumption or preference (Matthews et al, 1996; Shalev and Kafkafi, 2002; Matthews and Robbins, 2003; Ruedi-Bettschen et al, 2005), though few reports have indicated an increase in sucrose consumption and preference in maternally separated rats (Vazquez et al, 2005; Michaels and Holtzman, 2007). Regarding motivated behavior, maternal separation has been shown to either reduce the motivation for a sucrose reward (Ruedi-Bettschen et al, 2005; Ruedi-Bettschen et al, 2006; Leventopoulos et al, 2009) or have no effect on motivated responding (Shalev and Kafkafi, 2002), assessed using a progressive-ratio schedule of reinforcement.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on anhedonia-like behavior, thus sucrose consumption and sucrose preference, is also not consistent. While most authors report no effects of MS on sucrose preference (Shalev and Kafkafi 2002;Matthews and Robbins 2003), there are also reports of decreased sucrose preference compared to NH (Michaels and Holtzman 2007). Interestingly, when sucrose is not freely available but requires effort in terms of bar presses on a progressive ratio schedule, ED male Wistar rats have been shown to consume significantly less sucrose Leventopoulos et al 2009).…”
Section: Repeated Maternal Separation For 1-8 Hmentioning
confidence: 99%